Aplikasi Saran Buku Bacaan Bagi Pengunjung Perpustakaan AMIK STIEKOM Sumatera Utara Berdasarkan Algoritma Brute Force - Taronisokhi Zebua; Natalia Silalahi (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Service of information about books in a library is very helpful and makes it easier for visitors to find the book they want to find. Presentation of information on books available in the library of AMIK Stiekom North Sumatra has not been effective and efficient, because it is still done by looking at the library employee records on the list of books that have been provided. This problem becomes one of the factors to decrease interest in reading the library visitors. Utilization of application suggestions reading books in the library of AMIK Stiekom North Sumatra can be used as a trigger of the interest of visitors to keep reading books available in the library. The built-in book suggestion app works based on brute-force algorithms so that it can present book information relevant to the topic being searched by the visitors.